2016
DOI: 10.14198/jhse.2016.11.proc1.10
|View full text |Cite
|
Sign up to set email alerts
|

Can the intensity of game load affect the shooting performance in basketball?

Abstract: Victory in a basketball game depends on many factors. One of the main factors that determine game performance of the team is the successfulness of basketball shooting. The aim of this study is to determine the influence of the game load intensity on basketball shooting performance. Ten senior female basketball players (2 nd division) participated in this study. Bleep test was used to set the maximal heart rate (HRmax) of each player. The intensity of game load was classified as follows: <75, 75-84, 85-95, >95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…However, it is important to mention that 88% in the U19 category and up to 90% in the senior category of all shooting attempts were performed at an heart rate level higher than 85% of HR max as well as that the efficiency of the shooting performance progressively decreased with the increase of the heart rate level in both categories. Our finding can be compared to the results of previously published research reports (Vencúrik, 2016;Ardigò et al, 2018;Padulo et al, 2018) that found the negative influence of heart rate level on shooting Frontiers in Physiology frontiersin.org efficiency. More precisely, the study by Vencúrik (2016) found that female basketball players had 60%, 37.5%, and 45.2% successfulness in shooting with HR at the level <85% HR max , 85-95% HR max , and >95% HR max , respectively.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, it is important to mention that 88% in the U19 category and up to 90% in the senior category of all shooting attempts were performed at an heart rate level higher than 85% of HR max as well as that the efficiency of the shooting performance progressively decreased with the increase of the heart rate level in both categories. Our finding can be compared to the results of previously published research reports (Vencúrik, 2016;Ardigò et al, 2018;Padulo et al, 2018) that found the negative influence of heart rate level on shooting Frontiers in Physiology frontiersin.org efficiency. More precisely, the study by Vencúrik (2016) found that female basketball players had 60%, 37.5%, and 45.2% successfulness in shooting with HR at the level <85% HR max , 85-95% HR max , and >95% HR max , respectively.…”
Section: Discussionsupporting
confidence: 72%
“…Our finding can be compared to the results of previously published research reports (Vencúrik, 2016;Ardigò et al, 2018;Padulo et al, 2018) that found the negative influence of heart rate level on shooting Frontiers in Physiology frontiersin.org efficiency. More precisely, the study by Vencúrik (2016) found that female basketball players had 60%, 37.5%, and 45.2% successfulness in shooting with HR at the level <85% HR max , 85-95% HR max , and >95% HR max , respectively. In a similar vein, Padulo et al (2018) suggested that the efficiency of 2 PT shooting of male players at an heart rate level above 80% of HR max (30%) was significantly lower compared to the efficiency of shooting at the heart rate level of 50% of HR max (38.2%) and rest (42.3%).…”
Section: Discussionsupporting
confidence: 72%
“…the traditional definition of minutes played). This review identified a wide range of methods used to determine training duration in basketball, and a significant number of studies (n = 24) that failed to report how duration was defined and calculated [32,49,52,66,69,71,72,75,84,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. A commonly used description of duration methodology in basketball was defined in 1995 by McInnes et al [47], where total time was calculated as "all of the time that the subject was on the court, including all stoppages in play such as time-outs, free-throws and out-of-bounds, but excluding breaks between quarters, or time that the subject was substituted out of the game" [47].…”
Section: Methodology For Quantifying Durationmentioning
confidence: 99%
“…The difference in successfulness can probably be caused by different categorization of internal load. Vencúrik [36] reports a shooting success rate of 60%, 37.5%, and 45.16% for internal load <85% of HR max , 85-95% of HR max , and >95% of HR max , respectively. In the study mentioned above, the author did not find effect between the successfulness of the shooting and the internal load, which corresponds with our results.…”
Section: Internal Loadmentioning
confidence: 99%